Urban Flood and Its Correlation with Built-up Area in Semarang, Indonesia - Khoirunisa, Risty; Yuwono, Bambang Darmo (Smart City, 2023)
The expansion of urban areas is closely related to environmental problems such as changes in land use, flooding, and land subsidence. Semarang is a city with reasonably rapid development and a high land change experiencing floods and land subsidence. This paper will discuss land transformation caused by urban growth and its implications. It uses a combination of geospatial techniques and cloud computing Google Earth Engine (GEE) to carry out mapping over a large area without being constrained by computer capabilities. This study found that the built-up area in 2010 occupied 36.27% of the city, and it went up to 59.79% in 2021, in eastern, south-eastern, and northern parts of Semarang City in the last six years. Most of the built-up areas, especially those located in coastal areas, are located in areas with a high rate of land subsidence and urban flooding. The built-up area also significantly increases residential areas compared to other land cover types such as vegetation, open land, and water bodies. Built-up area growth also contributes to the rate of land conversion in Semarang City, especially in Mijen Regency; the vegetation cover was transformed into industrial areas and housing, which heavily stressed the land and environment. This leads to the increasing subsidence on the land of that area, which resulted in increasing tidal floods or rob.